Sealing Ability of Biodentine as a Retrograde Filling Materials (A Comparative in vitro study) - Makdad N. Chakmakchi; Maha M. Yahya; Wiaam M.O. AL-Ashou (University of Mosul, College of Dentistry, 2015)
Aim: Inadequate apical seal is the major cause of endodontic failure, the root end filling material used should prevent ingress of potential contaminants from periapical tissue. Aims: The purpose of this in vitro study was to evaluate the sealing ability of Biodentine (Septodent) when used as a root-end filling material and to compared the result with that of White Mineral Trioxide Aggregate ( MTA) and Glass Ionomer Cement (GIC). Materials and Methods: The root canals of (34) extracted human teeth were instrumented and obturated with gatta percha. Apexes were resected and cavities were prepared to 3mm depth. Teeth were divided randomly into three groups(n=10): first group was retrofilled with Biodentine, second with MTA, third group with GIC, and positive (n=2) and negative (n=2) control groups. Nail varnish was applied to all root surfaces except the tip of the root. Following immersion in basic fuchsine 1% , the roots were sectioned longitudinally and depth of dye penetration was evaluated by stereomicro-scope at 40X magnification. Data were analyzed using one way ANOVA and Duncan›s multiple range test at P< 0.05. Results: In this study, biodentine was determined to be superior than MTA and GIC prevention apical microleakage when used as root-end filling. No statistical significant difference was observed between MTA and GIC. Conclusions: under the conditions of this in vitro study, despite some variation, Biodentine provides a better seal than MTA and GIC when used as retro filling, but along term in vivo study is required to prove it